Non-Syndromic Familial Unerupted Teeth: A Rare Contidion - Akif Türer; İsmail Sener; Mehmet Bereket; Muhsin Ozdemir (Cumhuriyet Dental Journal, 2015)
A tooth that remains unerupted beyond the normal time of eruption and fails to erupt is called an impacted tooth. Maxillofacial surgeons encounter the problem of impacted teeth very often. Usually, impacted teeth involve the permanent dentition and they are rare in the primary dentition. Impaction of a primary tooth is a very rare entity. These rare cases are seen more frequently in primary second molars, followed by the order of the lower and upper centralincisor, lateral incisor and the canine teeth. Evolutionary and hereditary factors may cause uneruption. In this report, three cases of impacted primary teeth that belong to same familial members are presented. Father and sons. We extracted boy’s teeth but father refused treatment.